DEM-SPH study of molten slag trickle flow in coke bed. (16th January 2018) - Natsui, Shungo; Sawada, Akinori; Terui, Koki; Kashihara, Yusuke; Kikuchi, Tatsuya; Suzuki, Ryosuke O.
Graphical abstract: Highlights: DEM-SPH simulation was performed to capture the transient liquid surface flow. Over 10 million particles were tracked. Effect on hold up of the orthogonal projection for the packed structures was examined. Even in a complicated coke bed, the hold up characteristics can be determined depending on the individual their postures. Abstract: A fully-Lagrangian numerical model was applied for understanding packed bed structures containing non-spherical solids, such as coke, and the high-temperature melt trickle flow characteristics of such beds. Smoothed-particle hydrodynamics (SPH) simulations can track the motion of liquids without discriminating between continuous and dispersed phases, and the extended discrete element method (DEM) is employed as a highly accurate method for simulation of non-spherical solid-particle motion. Based on this model, we carried out large-scale trickle flow simulations using more than 10 million particles, investigated case studies of statistical processing, and evaluated the effects of packed bed formed from various non-spherical coke samples. We found that the pathway that the passing rivulet takes down depends on the structure of the void and the neck size between two voids. If the connecting neck is larger than the capillary length λ = σ / ρ g, the slag will drain. The shape of pathway was related that the solids shape factor which is considered by the projected area in the direction of gravity. Even if cokes with similar size were obtained by sieving, low sphericity cokes block slag flow through channeling voids, i.e., as the projected area of the non-spherical solid shape increased, the liquid hold up showed a tendency to increase.